The HOPS complex mediates autophagosome–lysosome fusion through interaction with syntaxin 17 - Jiang, Peidu (The American Society for Cell Biology, 2014)
Membrane fusion is generally controlled by Rabs, soluble N-ethylmaleimide–sensitive factor attachment protein receptors (SNAREs), and tethering complexes. Syntaxin 17 (STX17) was recently identified as the autophagosomal SNARE required for autophagosome–lysosome fusion in mammals and Drosophila. In this study, to better understand the mechanism of autophagosome–lysosome fusion, we searched for STX17-interacting proteins. Immunoprecipitation and mass spectrometry analysis identified vacuolar protein sorting 33A (VPS33A) and VPS16, which are components of the homotypic fusion and protein sorting (HOPS)–tethering complex. We further confirmed that all HOPS components were coprecipitated with STX17. Knockdown of VPS33A, VPS16, or VPS39 blocked autophagic flux and caused accumulation of STX17- and microtubule-associated protein light chain (LC3)–positive autophagosomes. The endocytic pathway was also affected by knockdown of VPS33A, as previously reported, but not by knockdown of STX17. By contrast, ultraviolet irradiation resistance–associated gene (UVRAG), a known HOPS-interacting protein, did not interact with the STX17–HOPS complex and may not be directly involved in autophagosome–lysosome fusion. Collectively these results suggest that, in addition to its well-established function in the endocytic pathway, HOPS promotes autophagosome–lysosome fusion through interaction with STX17.